GENETIC VARIABILITY, HERITABILITY AND EXPECTED GENETIC ADVANCES OF QUANTITATIVE CHARACTERS IN F2 PROGENIES OF SOYBEAN CROSSES - Hakim, Lukman; Suyamto, Suyamto; Paturohman, Eman (Indonesian Agency for Agricultural Research and Development - MOA, 2014)
The F2 progenies of crosses among three soybean varieties were evaluated with their parents at Ngale Experimental Farm, Ngawi, East Java during the dry season of 2011. The experi-ment was conducted in a randomized block design with three replications. The seeds of each F2 progenies and parents were planted in two rows of 4.5 m long. Plant spacing was 40 cm x 15 cm and each hill contained one plant. Among the characters studied, seed weight per plant, number of pods per plant and days to maturity had the highest coefficient of variability with the means of 52.6%, 48.2% and 41.9%, respectively. Whereas seed size, plant height and number of reproductive nodes had moderate values of 36.9%, 35.5% and 37.4%, respectively. Number of branches and days to flowering had the lowest variability of 11.7% and 15.3%, respectively. Number of pods per plant, days to maturity, plant height and seed size had high mean estimates of heritability coupled with high genetic advance. The genetic progress of these characters that would be obtained for one generation of selection was estimated 47.2%, 45.7%, 40.9% and 40.3%, respectively. Among the agronomic characters, plant height, number of pods per plant, seed size and days to maturity had the highest coefficient of variability associated with high heritability and genetic advance. Therefore, selection for high yielding with early maturity soybean genotypes based on plant height, number of pods per plant and seed size might be possible.